The Green Trade War: Legal Implications Of The Carbon Border Adjustment Mechanism On Indonesia’s International Trade - Jesslyn Huga Gracia; Zahwa Aulia; Daniel Christian P. L. Tobing (Program Magister Ilmu Hukum, Universitas Ekasakti, 2026)
This research is motivated by the growing global attention toward the Carbon Border Adjustment Mechanism implemented by the European Union as an effort to address carbon leakage and maintain the competitiveness of domestic industries. Most previous studies have primarily focused on the economic and trade dimensions, while discussions on the policy’s impact on developing countries such as Indonesia remain limited. This study aims to analyze how the implementation of this policy affects Indonesia’s trade dynamics and export competitiveness, as well as to provide insights for the development of national carbon regulation aligned with global mechanisms. The research employs a juridical-normative approach with qualitative analysis through a literature study of relevant legislation, international policies, and legal doctrines. The findings indicate that this policy potentially increases export costs and reduces the competitiveness of Indonesian products in the European market. However, it also presents an opportunity to strengthen Indonesia’s national carbon economic value system through regulatory harmonization, enhanced transparency in emission reporting, and the adoption of sustainable low-carbon technologies.